Membrane-Free Stem Cells and Pyridoxal 5'-Phosphate Synergistically Enhance Cognitive Function in Alzheimer's Disease Mouse Model - Ji Myung Choi; Hye Sook Park; Mei Tong He; Young Sil Kim; Hyun Young Kim; Ah Young Lee; Eun Ju Cho (MDPI AG, 2022)
Accumulation of amyloid beta (Aβ) is a major pathological hallmark of Alzheimer's disease (AD). In this study, we evaluated the protective effect of membrane-free stem cell extract (MFSCE), which is a component of adipose-tissue-derived stem cells, on cognitive impairment in Aβ25-35-injected AD mice. The ICR mice were i.c.v. injected with Aβ25-35 and then treated with MFSCE for 14 days (i.p.). The Aβ25-35-injected mice showed deficits in spatial and object perception abilities, whereas treatment with MFSCE inhibited Aβ25-35-induced learning and memory impairment in the T-maze, novel object recognition, and Morris water maze tests. Moreover, Aβ25-35-induced lipid peroxidation and nitric oxide overproduction were attenuated by treatment with MFSCE. These antioxidant effects of MFSCE were related to the inhibition of the apoptotic signaling pathway. In particular, the combination treatment of MFSCE and pyridoxal 5'-phosphate (PLP) showed greater suppression of Bax and cleaved caspase-3 protein expression compared to the MFSCE- or PLP-only treatment. Furthermore, the MFSCE and PLP combination significantly downregulated the amyloidogenic-pathway-related protein expressions, such as amyloid precursor protein, presenilin 1, and presenilin 2. Therefore, the MFSCE and PLP combination may synergistically prevent Aβ25-35-induced neuronal apoptosis and amyloidogenesis, which contributes to cognitive improvement and has potential therapeutic implications for AD patients.